LEADERSHIP DEFINITIONS APPLICATIONS FOR LECTURERS’ LEADERSHIP DEVELOPMENT - Reni Rosari (Journal of Leadership in Organizations, 2019)
Bernard M. Bass (1990), John P. Kotter (1988), and Joseph C. Rost (1993) defined leadership in different meanings. Among the three definitions, Rost’s definition can be as a practical application as well as providing guiding principles for lecturers’ leadership development. Leadership is not a person and it is different from management. Leadership is an influence relationship among leaders and followers who intend real changes that reflect their mutual purposes. Four essential elements that must be present if leadership exists are: (1) the relationship is based on influence, (2) leaders and followers are people in this relationship, (3) leaders and followers intend real changes, and (4) leaders and followers develop mutual purposes.